2017
DOI: 10.1007/s11999-017-5417-3
|View full text |Cite
|
Sign up to set email alerts
|

Does the Risk of Rerevision Vary Between Porous Tantalum Cups and Other Cementless Designs After Revision Hip Arthroplasty?

Abstract: Level III, therapeutic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 24 publications
0
27
0
1
Order By: Relevance
“…In the NJR for England and Wales we earlier reported lower revision rates for infection when TM (versus non-TM) was used in primary THA [9], but no difference in re-revision rates for infection when TM was used for all-cause revision THAs [11]. The latter findings in allcause revisions were also confirmed in a study from the Swedish and Australian registries [8]. It is possible that TM only reduces the risk of infection when it is specifically used for PJI revisions, rather than revisions for all-causes.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…In the NJR for England and Wales we earlier reported lower revision rates for infection when TM (versus non-TM) was used in primary THA [9], but no difference in re-revision rates for infection when TM was used for all-cause revision THAs [11]. The latter findings in allcause revisions were also confirmed in a study from the Swedish and Australian registries [8]. It is possible that TM only reduces the risk of infection when it is specifically used for PJI revisions, rather than revisions for all-causes.…”
Section: Discussionmentioning
confidence: 60%
“…Using the same registry we also earlier reported no difference in re-revision rates for infection when TM (versus non-TM) was used for 3,862 all-cause revision THAs [11]. Another study of 6,843 all-cause revisions from two large registries (Sweden and Australia) similarly showed that the re-revision rate for PJI was not different when TM or non-TM components were used at revision THA [8].…”
Section: Introductionmentioning
confidence: 60%
See 3 more Smart Citations